Chemical and population genetic analysis show no evidence of ecotype formation in a European population of the parasitoid wasp Nasonia vitripennis - Buellesbach, Jan; Lammers, Mark; van de Belt, José; Pannebakker, Bart A. (Frontiers in Ecology and Evolution, 2023)
Ecotypes, subpopulations or strains of a single species locally adapted to divergent ecological conditions are often considered to be the first steps in sympatric speciation. It has been suggested that two ecotypes are distinguishable in Nasonia vitripennis, a prominent model organism for parasitic Hymenoptera, with one ecotype parasitizing fly pupae in bird nests, and the other one parasitizing fly pupae on carrion. This differentiation into two ecotypes has been hypothesized to indicate incipient sympatric speciation in populations of this globally distributed species. In the present study, we investigated the differentiation into these two distinct ecotypes focusing on chemical profiles and the population genetic divergence in a wild N. vitripennis population from the Netherlands. Isofemale lines were obtained from bird nest boxes and from deer carrion, respectively, representing both microhabitats. To test for phenotypic differentiation, we determined the surface cuticular hydrocarbon (CHC) profiles from wasps of both host patches. Using a panel of 14 microsatellites, we concordantly determined the population genetic structure and tested for genetic differentiation between foundresses obtained from both microhabitats. Both the phenotypic as well as the genetic datasets show no evidence for any kind of separation based on the postulated two ecotypes, but rather suggest free interbreeding with no gene flow interruption between the two distinct host patches. Our findings challenge previous assumptions on clearly distinguishable ecotypes in N. vitripennis, and demonstrate how a chemical ecological assessment coupled with population genetics can be instrumental in re-evaluating the potential of ecological differentiation and incipient speciation mechanisms in parasitoid wasps.